The In-between Expression: Interpreting the Ambiguity of Islamic Culture in Bolaang Mongondow, North Sulawesi - Abdul, Moh. Rivaldi (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2024)
This article interprets the encounters between various elements—Islam and rites, syarak and custom, and the profane and sacred—in the development of Islam in Bolaang Mongondow, North Sulawesi. The interpretation is based on the theoretical framework of cultural ambiguity. By exploring the tolerance of ambiguity, compromise solutions, and divergent meanings, this study aims to reveal religious expressions that embody an "in-between" state. Utilizing a literature study approach with cultural and historical perspectives, the findings indicate that the tolerance of ambiguity allows Islam and local rites to coexist in this "in-between" expression. The integration of syarak and custom in the development of Islam in Bolaang Mongondow also highlights this "in-between" expression, adhering to the principle that customs contravening syarak are abandoned, while those not contravening are maintained. Additionally, the carving of thayyibah words in Islamic art in Bolaang Mongondow illustrates the divergent meanings between the profane and sacred. Ultimately, the encounters between these different elements coexist within the "in-between" expression, uniting them into a singular Islamic cultural expression.